Una nueva especie de Ficus (Moraceae) de la llanura amazónica peruana - Reynel Rodriguez, Carlos (2024)
A new species of Ficus L. (Moraceae) from Peru is here described, Ficus ucayaliensis Reynel & Albán. It belongs to the subgenus Pharmacosycea (Miq.) Miq., being distinct in several characters, both vegetative and reproductive, among them the notoriously elongated peduncle of the syconium; it is known from the Amazonian lowland of the department of Ucayali, in a mature riparian forest.